Intraseasonal to Interannual Variability of the Atlantic Meridional Overturning Circulation from Eddy-resolving Simulations and Observations - Xu, Xiaobiao; Chassignet, Eric P; Johns, William E; Schmitz, Jr, William J; Metzger, E J (2014)
Results from two 1/12 deg eddy-resolving simulations, together with data-based transport estimates at 26.5 deg N and 41 deg N, are used to investigate the temporal variability of the Atlantic meridional overturning circulation (AMOC) during 2004 2012. There is a good agreement between the model and the observation for all components of the AMOC at 26.5 deg N, whereas the agreement at 41 deg N is primarily due to the Ekman transport. We found that (1) both observations and model results exhibit higher AMOC variability on seasonal and shorter time scales than on interannual and longer time scales; (2) on intraseasonal and interannual time scales, the AMOC variability is often coherent over a wide latitudinal range, but lacks an overall consistent coherent pattern over the entire North Atlantic; and (3) on seasonal time scales, the AMOC variability exhibits two distinct coherent regimes north and south of 20 deg N, due to different wind stress variability in the tropics and subtropics. The high AMOC variability south of 20 deg N in the tropical Atlantic comes primarily from the Ekman transport of the near-surface water, and is modulated to some extent by the transport of the Antarctic Intermediate water below the thermocline. These results highlight the importance of the surface wind in driving the AMOC variability. Pub. in Journal of Geophysical Research: Oceans, p1-20, 2014.